Honoring elders : aging, authority, and Ojibwe religion - McNally, Michael David (Religion and American culture (New York, N.Y.), 2009)
Like many Native Americans, Ojibwe people esteem the wisdom, authority, and religious significance of old age, but this respect does not come easily or naturally. It is the fruit of hard work, rooted in narrative traditions, moral vision, and ritualized practices of decorum that are comparable in sophistication to those of Confucianism. Even as the dispossession and policies of assimilation have threatened Ojibwe peoplehood and have targeted the traditions and the elders who embody it, Ojibwe and other Anishinaabe communities have been resolute and resourceful in their disciplined resp.